EXTRAS (Fiep Bulletin - online, 2012)
PRINCE FAISAL BIN FAHAD INTERNATIONAL PRIZE FOR ARAB SPORT DEVELOPMENT RESEARCHESFIEP DELEGATESSTRUCTURE OF THE FIEP FIEP EXECUTIVE BOARD 2008-2012 ABOUT THE FIEP FIEP CROSS OF HONOR SUBSCRIPTION FORM PROGRAMACION DEL SEMINARIO: LA HISTORIA DE LA FIEP EN AMERICA